Influencia do conteúdo das palavras e da personalidade dos sujeitos na transmissão oral de informações - de Andrade Graciano, Marilia de Oswaldo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This study dealt with the ambiguity in message transmission as a function of the type of word being transmitted and the personality of the subject delivering the message. The following hypotheses were considered: (a) there are differences between introvert and extrovert subjects as to explicitness in the transmission of the message; (b) there are differences in the scores of the same subject due to type of word to be transmitted (objective or subjective meaning) ; (c) there is an interaction between the two independent variables (type of personality and type of word).